Boosting Online Sales for Micro, Small, and Medium Enterprises (MSMEs) at Bank Jatim Pasar Besar Madiun - Isbahi, Muhammad Baiqun; Ayad, Nahid; Alouzi, Khuloud Mustafa` (Yayasan Pendidikan Islam Bustanul Ulum Mojokerto, 2025)
Micro, small, and medium enterprises (MSMEs) are critical to Indonesia's economic growth; however, they continue to face significant challenges, particularly limited access to broader markets. The integration of digital technology, especially e-commerce, presents a strategic opportunity to overcome these constraints. This community engagement initiative, in collaboration with Bank Jatim Pasar Besar Madiun and participants of the Certified Independent Study Internship Program (MSIB), aimed to enhance the digital capabilities of MSMEs through a structured mentorship program known as Friends of Power. This program provided tailored assistance in adopting digital marketing strategies and accessing online sales platforms. The intervention employed the Asset-Based Community Development (ABCD) approach, emphasizing the utilization of local assets, and data were collected through systematic observation and documentation. Findings indicate that the application of digital tools and e-commerce strategies significantly contributed to increased visibility, business expansion, and income growth among participating MSMEs. This study demonstrates the potential of digitally-driven empowerment models to support MSME resilience and scalability, offering valuable insights for policymakers and development practitioners.